Depression And Anxiety In Patients With Juvenile Idiopathic Arthritis: Current Insights And Impact On Quality Of Life, A Systematic Review - Fair DC (Dove Medical Press, 2019)
Danielle C Fair,1 Martha Rodriguez,2 Andrea M Knight,3 Tamar B Rubinstein4 1Division of Pediatric Rheumatology, Medical College of Wisconsin: Children’s Hospital of Wisconsin, Milwaukee, WI, USA; 2Division of Pediatric Rheumatology, Indiana University School of Medicine, Indianapolis, IN, USA; 3Division of Pediatric Rheumatology, Hospital for Sick Children, Toronto, ON, Canada; 4Division of Pediatric Rheumatology, Albert Einstein College of Medicine: Children’s Hospital at Montefiore, Bronx, NY, USACorrespondence: Danielle C FairMCW Pediatric Rheumatology, Children’s Corporate Center, 999 N 92 nd St., Suite C465, Wauwatosa, WI 53226, USATel +1 414-266-2036Fax +1 414-266-6695Email dfair@mcw.eduAbstract: Depression and anxiety are prevalent in children with rheumatologic diseases, including juvenile idiopathic arthritis (JIA). However, prevalence rates and the relationship with disease outcomes, including quality of life are conflicting in the early literature. To review the current literature, determine gaps in our knowledge, and identify areas in need of further investigation, we conducted a systematic review of studies examining depression and anxiety symptoms among children with JIA and the impact these symptoms may have on disease outcomes and quality of life. Six electronic databases were searched up until January 2019. Of 799 potential articles, 60 articles were included with the main focus on 28 articles from 2009 to 2019, to concentrate on the most current evidence. We found that JIA patients experience symptoms of depression and anxiety similar to other childhood chronic diseases and at higher rates than in healthy children. Patients who experience these symptoms have worse quality of life, with some evidence pointing to depression and anxiety symptoms having a greater impact on quality of life than other disease features, such as active joint count. Family members of JIA patients experience high rates of anxiety and depression symptoms which may impact their child’s mental health and pain symptoms related to JIA. Conflicting reports of associations between depression/anxiety symptoms and disease features/disease outcomes and a paucity of longitudinal studies investigating the impact of treatment on mental health symptoms indicate areas in need of further research to effectively identify patients at greatest risk of depression and anxiety and to better understand how to treat and prevent these symptoms in youth with JIA. Family mental health should also be considered in investigations concerning mental health and disease outcomes of children with JIA.Keywords: pediatric rheumatology, mental health, mood disorder, arthritis, autoimmune disease